Atraumatic splenic rupture associated with apixaban. (February 2019) - Basnet, Sijan; Mohanty, Elan; Mir, Izza; Dhital, Rashmi; Koirala, Ajay; Tachamo, Niranjan
Apixaban is a direct oral anticoagulant that works by inhibiting factor Xa. It has been associated with adverse bleeding outcomes including atraumatic splenic rupture. We present the case of an 86-year-old man who presented with features of left upper abdominal pain and hemorrhagic shock found to have atraumatic splenic rupture and hemoperitoneum on imaging.